Common Fixed Points Within Framework of F-Modular b-Metric Space and Its Applications - Parveen Tyagi; Surjeet Singh Chauhan (Gonder); Naveen Mani; Rahul Shukla (Abstract and Applied Analysis)
MSC2010 Classification: 47H10, 54H25